One Year Into the Pandemic: A Systematic Review of Perinatal Mental Health Outcomes During COVID-19 - Iyengar, Udita; Jaiprakash, Bhavisha; Haitsuka, Hanako; Kim, Sohye (Frontiers in Psychiatry, 2021)
Obstetric guidelines have rapidly evolved to incorporate new data and research on the novel coronavirus disease (COVID-19), with data on perinatal mental health building over the last year. Our aim in the present manuscript is to provide a systematic review of mental health outcomes in pregnant and postpartum women during the COVID-19 pandemic in the context of neonatal and obstetric guidelines addressing symptoms and complications of COVID-19 during pregnancy, mother-to-neonate transmission, Caesarean-section delivery, neonatal prematurity, maternal/neonate mortalities, maternal-neonatal separation, and breastfeeding. We summarize data from 81 mental health studies of pregnant and postpartum women and underscore protective and risk factors identified for perinatal mental health outcomes amidst the COVID-19 pandemic. Data reviewed here suggest increased psychological symptoms, especially depressive and anxiety symptoms, in pregnant and postpartum women during COVID-19. Our systematic review integrates the most current obstetric and neonate guidelines, along with perinatal mental health outcomes associated with COVID-19, highlighting the best available data for the care of women and their neonates amidst the current COVID-19 pandemic.